The Effect of Sufentanil Administration on Remifentanil-Based Anaesthesia during Laparoscopic Gynaecological Surgery: A Double-Blind Randomized Controlled Trial. (13th May 2014) - Son, Ilsoon; Oh, Chung-Sik; Choi, Jae Won; Kim, Seong-Hyop
Abstract : This study assessed the effect of sufentanil administered before conclusion of remifentanil-based anaesthesia on postoperative hyperalgesia and haemodynamic stability in patients undergoing laparoscopic gynaecological surgery. The patients were randomly allocated to a sufentanil administration group (S group) or a normal saline administration group (C group). Anaesthesia was induced and maintained with controlled administration of remifentanil at 10 ng·mL −1 and propofol under bispectral index guidance. Once the surgical specimen was procured, sufentanil or normal saline was administered at 0.15 ng·mL −1 and maintained until extubation. The haemodynamic status during anaesthetic emergence was evaluated. The pain and postoperative nausea and vomiting (PONV) were assessed for 72 h following postanaesthetic care unit (PACU) discharge. The S group had significantly lower mean systemic arterial blood pressure and heart rate changes between the start of drug administration and extubation. Postoperative pain was significantly lower in the S group until 24 h following PACU discharge. There were no significant differences in PONV incidence and severity 72 h after PACU discharge between the two groups. Sufentanil administration before concluding remifentanil-based anaesthesia improved postoperative hyperalgesia and achieved haemodynamic stability at extubation without delaying recovery or increasing PONV during laparoscopic gynaecological surgery. Clinical trial registration is found at KCT0000785 .